2009
DOI: 10.1074/jbc.m109.025353
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Elevation in Mitochondria Is the Main Ca2+ Requirement for Mitochondrial Permeability Transition Pore (mPTP) Opening

Abstract: We have investigated in detail the role of intra-organelle Ca2+ content during induction of apoptosis by the oxidant menadione while changing and monitoring the Ca2+ load of endoplasmic reticulum (ER), mitochondria, and acidic organelles. Menadione causes production of reactive oxygen species, induction of oxidative stress, and subsequently apoptosis. In both pancreatic acinar and pancreatic tumor AR42J cells, menadione was found to induce repetitive cytosolic Ca2+ responses because of the release of Ca2+ from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(167 citation statements)
references
References 57 publications
3
159
0
5
Order By: Relevance
“…We applied an oxidative stress, that is, treated the cells acutely with 1 mM H 2 O 2 . As previously reported, 23 the addition of H 2 O 2 caused a [Ca 2 þ ] cyt increase that is much smaller and more sustained than that evoked by histamine (Figures 6a and b). Under those conditions, mitochondria also undergo a small increase (peak value o1 mM).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We applied an oxidative stress, that is, treated the cells acutely with 1 mM H 2 O 2 . As previously reported, 23 the addition of H 2 O 2 caused a [Ca 2 þ ] cyt increase that is much smaller and more sustained than that evoked by histamine (Figures 6a and b). Under those conditions, mitochondria also undergo a small increase (peak value o1 mM).…”
Section: Resultssupporting
confidence: 86%
“…À7.5 ± 2.5%; siRNA-hVDAC1 27.4 ± 1.5%; siRNA-hVDAC2 À45.9 ± 3.5%; c, Control À6.5 ± 2.1%; siRNA-hVDAC1 þ 30.9 ± 3.9%; siRNA-hVDAC2 À45.2 ± 2.3%; d, Control À4 ± 5.3%; siRNA-hVDAC1 þ 24.3 ± 5.1%; siRNA-hVDAC2 À50.1 ± 6.8%) 23 This latter event has been proposed to represent a sort of priming signal that conditions and sensitizes mitochondria to otherwise non-lethal stimuli. In this context, the local coupling between ER and mitochondrial Ca 2 þ channels becomes critically relevant: small Ca 2 þ microdomains elicited by apoptotic stimuli such as C2-ceramide strongly relies on the existence of a preferential route transmitting the signal from the ER to the mitochondrion; on the other side, during physiological signals large Ca 2 þ microdomains are generated and this fine channel coupling could be potentially overwhelmed by the vigorous ER Ca 2 þ release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative stressor induces two independent apoptotic pathways within pancreatic acinar cells, viz., the classical mitochondrial calcium-dependent pathway that is initiated rapidly in the majority of cells, and a slower, caspase-8-mediated pathway that depends on the lysosomal activities of cathepsins and is used when the caspase-9 pathway is disabled (Baumgartner et al, 2007). The present study demonstrated that HL-60 cells induced high caspase-8 activity and led to the cleavage of Bid protein without the MTP reduction.…”
Section: Discussionmentioning
confidence: 47%
“…Вплив О-карбоксиметилгідроксиламіну (О-СМН; 50 мг/кг) на показники кардіодинаміки ізольованого серця щурів за умов збільшення концентрації кальцію у перфузій-ному розчині: а -тиск у лівому шлуночку; б -коронарний потік; в -швидкість скорочення міокарда; г -інтенсивність скоротливої функції; 1 -контроль, 2 -дія О-СМН Пригнічення мітохондріального шляху синтезу сірководню погіршує скоротливу функцію серця серця та мітохондріях знижується, а відтак серце стає більш чутливим до ішемічно-ре-перфузійного пошкодження [13]. Окрім того, що Са 2+ регулює перебіг циклу Кребса та є активатором низки інших ферментів, у високій концентрації -це при-родний індуктор відкривання МП перемінної проникності [14]. У попередніх досліджен-нях було виявлено, що донор сірководню NaHS, внесений екзогенно у концентрації 10 -5 моль/л, попереджає відкривання МП, що проявлялося у зниженні набухання органел на тлі дії кальцію порівняно з таким у кон-трольних тварин [15].…”
Section: результати та їх обговоренняunclassified